Biowaste-derived Si@SiOx/C anodes for sustainable lithium-ion batteries. (20th January 2022) - Liu, Shih-Fu; Kuo, Chun-Han; Lin, Chia-Ching; Lin, Hung-Yuan; Lu, Cheng-Zhang; Kang, Jin-Wei; Fey, George Ting-Kuo; Chen, Han-Yi
Abstract: In this study, rice husks and waste coffee grounds (WCGs) are utilized as precursors for synthesizing Si@SiOx /C composite anode materials. The magnesiothermic method is applied to reduce the nano-sized silica derived from rice husks to Si@SiOx . The Si@SiOx product is then mixed with WCGs and carbonized at a high temperature to produce Si@SiOx /WCGC. After optimization, the Si@SiOx /WCGC with a precursor ratio of 1:2 provides a high reversible capacity of 1125 mA h g −1 at 100 mA g −1 . The capacity retention of Si@SiOx /WCGC (1:2) is 80% after 100 cycles at 1 A g −1, which is considerably higher than that of pristine Si@SiOx (only 1.8%). In addition, the lithium-ion diffusivity of Si@SiOx increased from 2.7 × 10 −12 to 4.5 × 10 −11  cm 2 s −1 after it is combined with the WCGC. Furthermore, a full cell using Si@SiOx /WCGC (1:2) as the anode and LiNi0.5 Mn1.5 O4 as the cathode is assembled, which exhibits a high energy density of 396 W h kg −1 . This demonstrates that biowaste-derived Si@SiOx /WCGC is a promising and environmentally friendly anode material for lithium-ion batteries.